Pemanfaatan Sistem Pendukung Keputusan Untuk Penentuan Alokasi Dana Kegiatan Berbasis Web Menggunakan Metode Object Oriented Analisis Design Dan Unified Modeling Language (Studi Kasus SMK Negeri 1 Cikarang Utara) - Muhamad Fatchan (Teknik Informatika, Universitas Pelita Bangsa, 2020)
The development of technology in the current era runs very rapidly, this is evidenced by the many uses of the internet network in various communities today. The use of computers has evolved from merely processing data or presenting information to management, to being able to provide choices as a decision support tool for management. Computer-based information systems (Computer Based on Information Systems), one of which is a Decision Support System (Decision Support System), which is an interactive computer information system that can provide alternative solutions for decision makers. At SMK N 1 Cikarang Utara the process of submitting an activity proposal has not been computerized and does not yet have a decision support system for determining the allocation of activity funds. So it must take a long time to verify the proposed activity proposal. The development of information technology has enabled decision makers to be done more quickly and accurately. So as to make decisions more quickly, carefully avoid and reduce the subjectivity of the resulting decisions needed a decision support system that aims to facilitate the process of verifying the proposal of activities and determination of activity funds for student activity units through the process of determining the feasibility of activities and allocation of funds given to carry out activities the. To get a solution to the problem of submission of proposals so that only incoming proposals that are in accordance with the criteria specified by the School Principal so that there is no prolonged revision process and no difficulty in processing proposal data, a website- based decision making system is designed. data collection methods using interview, observation and literature study methods, while in the design of information systems the author uses the Object Orientied Analyst Design